IMPLEMENTATION OF THE ELDERLY FOOD PROGRAM FOR SINGLE FAMILY CARDS IN CINANGKA DISTRICT - Ludwina Yuvani, Syallum; Rahmawati (NIAGARA Scientific Journal, 2026)
This research is motivated by the large number of Single Elderly who have limitations in meeting decent old age needs and their basic living needs are not met. Therefore, the Government through the Ministry of Social Affairs and Community Groups (POKMAS) strives for the welfare of the elderly through a food program. This study aims to determine the Implementation of the Single Family Card Elderly Food Program in Cinangka District using the Van Metter and Van Horn policy implementation model. This research method uses a descriptive qualitative method. Informants in this study were the Serang Regency Social Service, POKMAS Cinangka, Social Welfare Workers of Cinangka District, Head of Social Welfare Section of Cinangka District, Elderly Beneficiaries aged 75 years and over, and community leaders. The results of this study indicate that the Implementation of the Single Family Elderly Food Program in Cinangka District has a clear mechanism and legal basis, however, in its implementation it still faces several obstacles so that it is not fully optimal. The research recommendations are to increase the number of resources, provide more adequate facilities and infrastructure and build more effective and equitable collaboration and communication with program implementers at all levels